From Exclusion to Inclusion: Deaf and Hard-of-Hearing Students in the Spanish University - López Torrijo, Manuel (Education Policy Analysis Archives, 2008)
The educational inclusion of disabled people constitutes one of the most relevant educational and pedagogical innovations in the past decades. This article analyses such inclusion at the university level choosing students with deafness as a representative and extrapolative sample. After specifying the main limitations and needs for this group of students, the study revises the solutions put forward by the current legislation and it details in depth, by way of a comparative study, the services provided now by the newly created University Services for the Integration of students with special educational needs. The study points out conclusively some proposals for the future?principles, strategies, services, resources?which may enable to attain an equalitarian society through an educational integration in this higher stage of education.